PELATIHAN MANAJEMEN KELAS, DISIPLIN POSITIF DAN PEMANFAATAN PLATFORM DIGITAL GEMINI AI UNTUK ASESMEN PESERTA DIDIK - Pebrianti, Peby; Pipih; Maharani, Puan; Selviana, Putri; Sunita, Ragil; Abdul Karim; Sri Maryanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This community service initiative aims to enhance teachers' capabilities regarding classroom management, positive discipline in instruction, and the use of the Gemini AI digital platform for student assessment. The article discusses the integration of classroom management, positive discipline, and the application of Gemini AI for student assessment. The methodology employed involved training and mentoring conducted via workshops focused on classroom management, positive discipline, and the use of Gemini AI for assessment purposes. Nine teachers from SDN 3 Panembahan participated in the training. The sessions emphasized the importance of planning, implementation, evaluation, and monitoring as key components of classroom management, alongside the role of technology in facilitating effective classroom administration. Evaluation results indicate that the teachers utilized Gemini AI to create innovative assessments and were motivated to incorporate AI technology specifically Gemini into their teaching practices. By understanding and applying these concepts, teachers can improve their skills, thereby positively impacting the quality of instruction and student development.